Critical Biofilm Growth throughout Unmodified Carbon Felts Allows Continuous Bioelectrochemical Chain Elongation from CO2 up to Caproate at High Current Density - Jourdin, Ludovic; Raes, Sanne M. T.; Buisman, Cees J. N.; Strik, David P. B. T. B. (Frontiers in Energy Research, 2018)
Current challenges for microbial electrosynthesis include the production of higher value chemicals than acetate, at high rates, using cheap electrode materials. We demonstrate here the continuous, biofilm-driven production of acetate (C2), n butyrate (nC4), and n-caproate (nC6) from sole CO2 on unmodified carbon felt electrodes. No other organics were detected. This is the first quantified continuous demonstration of n-caproate production from CO2 using an electrode as sole electron donor. During continuous nutrients supply mode a thick biofilm was developed covering the whole thickness of the felt (1.2 cm deep), which coincided with high current densities and organics production rates. Current density reached up to -14 kA m-3electrode (-175 A m-2). Maximum sustained production rates of 9.8 ± 0.65 g L-1 day-1 C2, 3.2 ± 0.1 g L-1 day-1 nC4, and 0.95 ± 0.05 g L-1 day-1 nC6 were achieved (averaged between duplicates), at electron recoveries of 60-100%. Scanning electron micrographs revealed a morphologically highly diverse biofilm with long filamentous microorganism assemblies (~400 µm). n-Caproate is a valuable chemical for various industrial application, e.g. it can be used as feed additives or serve as precursor for liquid biofuels production.